Defluoridation of reject water from a reverse osmosis unit and synthetic water using adsorption. (June 2018) - Samrat, Maruvada V.V. Naga; Kesava Rao, K.; SenGupta, Arup K.; Riotte, Jean; Mudakavi, J.R.
Graphical abstract: Highlights: Fluoride can be removed from the reject water of a reverse osmosis unit using adsorption. The presence of HCO 3 − and SO 4 2 − has an adverse effect on defluoridation. Zirconium oxide nanoparticles embedded in a resin and activated alumina were used. The presence of small amounts of HCO 3 − leads to an increased uptake of F − . The cost of treated water ranges from Rs. 0.1–11.5/L (US 0.002–0.023/L). Abstract: Many parts of the world have excess fluoride in drinking water. At some locations, nitrate is also in excess. Hence, reverse osmosis (RO) units have been installed at several villages in India. Reverse osmosis is a good technique, but it has the disadvantage of discarding a considerable amount of the inlet water as a reject stream. This is an unsustainable way of using water. Two adsorbents, namely, a hybrid anion exchange resin embedded with zirconium oxide nanoparticles (HAIX-Zr), and activated alumina (AA) were used in column experiments. For water containing only F −, HAIX-Zr had a better capacity than AA. The same trend was observed with synthetic water samples containing other ions in addition to F - . However, for RO reject, the converse was true, and the capacities of AA and HAIX-Zr decreased significantly. For AA, the presence of a small concentration of HCO 3 − increased the uptake of F - by 100% compared to water containing only F - . For HAIX-Zr, the adsorption capacity decreased as the concentration of co-ions increased. The cost of treated water varied from 0.1–1.5/L (US $ 0.002–0.03/L) for AA and 0.2–11.5/L (US $ 0.004–0.23/L) for HAIX-Zr.